CRM performance and development of media entrepreneurship in digital, social media and mobile commerce. Issue 1 (4th September 2019) - Ebrahimi, Pejman; Ahmadi, Mahsa; Gholampour, Abbas; Alipour, Hamidreza
Abstract : Purpose: The purpose of this paper is to evaluate the effect of CRM performance and technological innovation on performance of media entrepreneurs considering firm size. Design/methodology/approach: This is an analytical study used to empirically test the hypotheses proposed for SEM techniques using PLS and R packages. It used two steps in this way: the assessment of the outer model and the assessment of the inner model. Moreover, a bootstrapping method was employed to test indirect effects. Data were collected by distributing 127 questionnaires between the managers and deputies of active firms across Rasht, Iran. Findings: The effect of CRM performance on SMEs performance development is partially mediated by media entrepreneurship. Moreover, the effect of technological innovation on SMEs performance development is mediated by media entrepreneurship. Furthermore, permutation test results indicated that there is no significant difference between small- and medium-sized firms. Research limitations/implications: This study used cross-sectional sampling method that can seriously limit result generalization. Therefore, conducting longitudinal studies is strongly recommended. Practical implications: The results of IPMA matrix indicated the serious importance of technological innovation, as a variable with the highest importance for SMEs performance development. Nevertheless, this variable has received the lowest importance in the studied population. Therefore, SMEs' managers should pay sufficient attention to the concepts of "product innovations" and "process innovations." Originality/value: This study is of high importance in that it has adopted new and effective indices for statistical analysis. IPMA matrix, permutation test, CTA and FIMIX are examples. In addition, plspm and Matrixpls packages in R were used for the first time in this study.